Tinjauan Hukum Tentang Pelaksanaan Pernikahan Siri Di Desa Pekan Heran Kecamatan Rengat Barat Kabupaten Indragiri Hulu Menurut Undang-Undang Perkawinan Nomor 1 Tahun 1974: Legal Overview of the Conduct of Siri's Marriage In Pekan Heran Village, Rengat Barat District, Indragiri Hulu Regency According to the Marriage Law Number 1 of 1974 - Ridhanti, Anissa; Fitra, Rahmat; Hamzah, Rosyidi (Jurnal Kajian Ilmu Hukum, 2022)
Abstrak Pernikahan siri secara agama dikatakan sah, namun sangat bertentangan dengan hukum positif di Indonesia. Sehingga akibat dari pernikahan siri ini menimbulkan banyak masalah dan kerugian yang ditujukan kepada perempuan. Padahal, masyarakat sudah banyak melakukan pernikahan siri ini sejak zaman dahulu. Penelitian ini dilakukan untuk mengetahui pelaksanaan pernikahan siri di Desa Pekan Heran Kecamatan Rengat Barat Kabupaten Indragiri Hulu beserta akibat hukum yang ditimbulkan menurut Undang-Undang Perkawinan Nomor 1 Tahun 1974. Metode penelitian yang digunakan yaitu penelitian hukum empiris dengan cara survey ke lapangan dan jenis penelitiannya deskriptif yakni menggambarkan penelitian yang jelas dan lengkap. Berdasarkan penelitian, penulis menyimpulkan pelaksanaan pernikahan di Desa Pekan Heran tidak dicatatkan di Kantor Catatan Sipil, guna untuk menjamin kepastian hukum dan memudahkan urusan administrasi di kemudian hari. Lalu, akibat hukum dari pernikahan siri ini adanya pihak dirugikan seperti istri dan anak. Bagi istri, ia tak dapat menuntut haknya berdasar hukum di Indonesia dan bagi anak yang lahir dari hasil pernikahan siri, tentunya membuat anak tak dapat mewarisi pihak ayahnya. Ia dianggap mempunyai hubungan perdata dengan ibunya dan keluarga ibunya saja. Abstract Unregistered marriage is said to be legal, but it is against positive law in Indonesia. So as a result of this unregistered marriage caused many problems and losses aimed at women. In fact, many people have done this series of marriages since ancient times. This research was conducted to determine the implementation of unregistered marriages in Pekan Heran Village, West Rengat District, Indragiri Hulu Regency and the legal consequences caused according to Marriage Law Number 1 of 1974. The research method used is empirical legal research by means of field surveys and the type of research is descriptive. which describes the research clearly and completely. Based on the research, the authors conclude that the implementation of marriages in Pekan Heran Village is not registered at the Civil Registry Office, in order to ensure legal certainty and facilitate administrative affairs in the future. Then, the legal consequence of this unregistered marriage is that there are disadvantaged parties such as wives and children. For a wife, she cannot claim her rights under Indonesian law and for a child born from an unregistered marriage, of course, the child cannot inherit his father's side. He is considered to have a civil relationship with his mother and only his mother's  Abstract Unregistered marriage is said to be legal, but it is against positive law in Indonesia. So as a result of this unregistered marriage caused many problems and losses aimed at women. In fact, many people have done this series of marriages since ancient times. This research was conducted to determine the implementation of unregistered marriages in Pekan Heran Village, West Rengat District, Indragiri Hulu Regency and the legal consequences caused according to Marriage Law Number 1 of 1974. The research method used is empirical legal research by means of field surveys and the type of research is descriptive. which describes the research clearly and completely. Based on the research, the authors conclude that the implementation of marriages in Pekan Heran Village is not registered at the Civil Registry Office, in order to ensure legal certainty and facilitate administrative affairs in the future. Then, the legal consequence of this unregistered marriage is that there are disadvantaged parties such as wives and children. For a wife, she cannot claim her rights under Indonesian law and for a child born from an unregistered marriage, of course, the child cannot inherit his father's side. He is considered to have a civil relationship with his mother and only his mother's family.